OPEN INNOVATION AND PERFORMANCE NEXUS: ROLE OF EMPLOYEE COMMITMENT, CULTURE, AND INNOVATION CLIMATE - Hieu Minh Vu (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Firms are increasingly depending on information and research collaboration from outside and within to develop products, services and processes that create value for stakeholders. The purpose of this paper is to develop a framework and suggest future research agenda for researchers to empirically establish the moderating effect of employee commitment, culture, and innovation climate. The empirical literature has been reviewed on open innovation and firm performance. Based on our review, a conceptual model and propositions for future research opportunities are identified. The proposed framework highlights the different measures of open innovation, firm performance, employee commitment, national culture and innovation climate. Our model can be applied to similar situations in different organisational settings and countries. Validating this model will enrich management and open innovation literature by providing insights into how employee commitment, national culture and innovation climate hinder or enhance inbound, outbound and coupled open innovation activities and performance.